Population Densities of the Plum scale Insect, Parlatoria oleae (Colvee) (Hemiptera: Diaspididae) in relation to the Resultant yield of Mango Fruits - El-Zoghby, Islam R.M.; Bakry, Moustafa M.S.; El-Rahman, Amira S.A. Abd (International Journal of Environment, Agriculture and Biotechnology, 2019)
The main objective of this work is to evaluate the relationship between the pest population, Parlatoria oleae (Colvee), through pest activity peaks in October/November; April and July on the yield loss of seedy Balady mango trees at Esna district, Luxor Governorate, Egypt through two seasons (2016/2017 and 2017/2018). Data revealed that the increment of population density caused gradual decrease of the yield of mango fruits, consequently increased the percentage of yield loss when the data of the yield were colligated with the pest population peaks in October/November; April and July months through 2016/2017 and 2017/2018 seasons. Increasing one individual of pest per leaf caused a reduction of the mango yield by 2.53, 2.51 and 4.59 kg/tree and 2.25, 2.19 and 2.88 kg/tree through the periods of population abundance of the two seasons, respectively. Accordingly, increased yield loss percentages by 1.05, 1.04 and 1.90% and 0.87, 0.84 and 1.10% occurred during the mentioned periods of the two consecutive seasons (2016/2017 and 2017/2018), respectively. These results confirmed that P. oleae population during the peak of April resulted the least expected amount of mango fruits yield and the greatest loss in mango yield. On contrary, the peak during July was less effective, causing the highest expected yield and the lowest reduction in mango fruits yield of the two seasons. Generally, the reduction in yield of mango fruits is known to be a summation of many factors including the rate of infestation, time of infestation and variety ability to infestation.